Development of Caregiver Empowerment Model in Caring for Mothers with Gestational Diabetes Mellitus - Teresia Retna Puspitadewi; Roudlotul Jannah; Yasin Wahyurianto (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Gestational Diabetes Mellitus (GDM) is a condition of elevated blood glucose levels during pregnancy, usually around 24 weeks of gestation, and contributes to approximately 3 million stillbirths annually. It increases the maternal mortality risk up to four times and poses long-term health risks. More than 50% of women with GDM are at risk of developing type 2 diabetes mellitus later in life. This study aims to develop a caregiver empowerment model for supporting mothers with GDM, based on the caregiver empowerment theory with a family-centred nursing approach. Methods: This model focuses on family caregiver factors and maternal GDM factors, as well as their influence on filial values, resources, appraisal, and caregiver outcomes. This study employs an explanatory design with a cross-sectional approach. The population comprises family caregivers of mothers with GDM who visited six community health centres (Puskesmas) in Tuban Regency. A total of 81 caregivers meeting the inclusion criteria were selected through systematic random sampling. Research variables include family caregiver factors, maternal GDM factors, filial values, resources, appraisal, and caregiver outcomes. Data were collected via questionnaires and analysed using Structural Equation Modelling-Partial Least Squares (SEM-PLS) after validity and reliability testing. Results: The results indicate that family caregiver factors (X1) significantly influence filial values (X3) and caregiver outcomes (Y1), while resources (X4) significantly affect appraisal (X5), with a T-value above 1.96 and a positive coefficient. The finding this model provides a new conceptual and practical contribution to maternal health interventions, particularly in strengthening family-based support systems for GDM management. Conclusion: In conclusion, the caregiver empowerment model for supporting mothers with GDM demonstrates that family caregiver factors influence filial values and caregiver outcomes, while resources affect appraisal.